Spiritual Branding and Corporate Profit in the Japanese Modern Mystery School - Christopher, Stephen (Implicit religion, 2022)
This article analyzes the irreducibility of spiritual branding, theologies of self-divinity and the business practices of a global esoteric company. Based on fieldwork with the Modern Mystery School (MMS) in Tokyo, I show how initiates, by purchasing an ascending syllabus of esoteric courses, recognize their own divinity and parlay this recognition into a spiritual brand that helps them market to their own clientele niche. The spiritual transformation of recognizing one's transcendent individual royalty is necessarily monetized as Adepts transition from paying clients to income-generating spiritual therapists. Parallel to this, top leadership have consciously fused MMS as an ancient hermetic lineage with a modern-day entertainment company, fashion company and lifestyle magazine. This has given MMS in Japan a recognizable public aesthetic which, combined with teachings about opposite but complementary Divine Masculinity and Femininity, advances gender normative ideologies often experienced by followers as spiritual alternativity. This article theorizes the intertwined relationship of other-worldly self-branding and this-worldly business acumen without reifying the binary between religion and economy or reducing meaningful spiritual transformation to corporate profit.